2021
DOI: 10.1016/j.jpra.2021.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing exposure to dermoscopy in plastic surgery training programs

Abstract: Summary Background Dermoscopy is a noninvasive tool that improves the diagnostic accuracy of melanoma and other cutaneous malignancies; yet, it is not widely used by plastic surgeons, who commonly manage skin lesions. Thus, the purpose of this study was to explore current practice patterns and knowledge of dermoscopy among plastic surgeons and postgraduate plastic surgery trainees. Additionally, interest to establish a formal dermoscopy curriculum as part of plastic surgery residency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…4,6 If dermoscopy is also integrated into the standard armamentarium of plastic surgeons, Percival et al conducted a survey using an electronic questionnaire to investigate dermoscopic activity among plastic surgeons and plastic surgery trainees at two Canadian universities. 10 The majority of participants were knowledgeable about the methodology of dermoscopy (n = 26; 96%), but only one participant reported using it in clinical practice. Nevertheless, all the participants indicated that they were involved in melanoma care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,6 If dermoscopy is also integrated into the standard armamentarium of plastic surgeons, Percival et al conducted a survey using an electronic questionnaire to investigate dermoscopic activity among plastic surgeons and plastic surgery trainees at two Canadian universities. 10 The majority of participants were knowledgeable about the methodology of dermoscopy (n = 26; 96%), but only one participant reported using it in clinical practice. Nevertheless, all the participants indicated that they were involved in melanoma care.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of training and access to dermatoscopes were the reasons why participants did not use a dermoscope. 10 In another study, Vahedi et al conducted a telephonic survey among trainees across plastic surgery units in the United Kingdom. 11 The response rate was 50% (n = 19/38), and 95% of respondents (n = 18) were knowledgeable about the tools used to diagnose melanocytic lesions, while 89% (n = 17) were familiar with dermatoscopes.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, dermoscopy has been applied not only to pigmented diseases but also to vascular lesions, among other lesion types 16) . Diagnostic programs based on deep learning are also being developed and plastic surgeons should learn how to apply them as standard procedures 17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Skin malignancies of the head and neck (H&N) in particular may present to and be treated by various clinicians such as general practitioners, dermatologists, plastic surgeons and oral and maxillofacial surgeons 2 . These clinical specialities receive different training [7][8][9] and a dermoscopic AI model may help in diagnostic equity and level the playing field. However, such a model must be validated on external datasets and perform well on skin lesions from different sites.…”
Section: Introductionmentioning
confidence: 99%